Reconstruction of hadronic decay products of tau leptons with the ATLAS experiment - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (The European physical journal. C, Particles and fields, 2016)
This paper presents a new method of reconstructing the individual charged and neutral hadrons in tau decays with the ATLAS detector. The reconstructed hadrons are used to classify the decay mode and to calculate the visible four-momentum of reconstructed tau candidates, significantly improving the resolution with respect to the calibration in the existing tau reconstruction. The performance of the reconstruction algorithm is optimised and evaluated using simulation and validated using samples of Z→ττ and Z(→μμ)+jets events selected from proton–proton collisions at a centre-of-mass energy s√=8TeV, corresponding to an integrated luminosity of 5 fb−1.
*ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A.E. Baas, O. Brandt, Y. Davygora, J.I. Djuvsland, M. Dunford, M.P. Geisler, M. Giulini, P. Hanke. J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, M. Sahinsoy, S. Schaetzel, V. Scharf, S. Schmitt, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und sehr viele weitere Personen]
Gesehen am 04.06.2020